Fuzzing para o Protocolo TLS: Estado da Arte e Comparação de Fuzzers Existentes - Velozo, Filipe T.; Ferreira, Thiago D.; Pacheco, Eduardo F.; Alves, Renan C. A.; Simplicio Jr., Marcos A.; Albertini, Bruno C.; Batista, Daniel M. (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2023: Companion Proceedings of the 23rd Brazilian Symposium on Information and Computational Systems SecurityDO - 10.5753/sbseg_estendido.2023.235133, 2023)
Among the various ways to verify the implementation of a protocol, fuzzing tests are worth mentioning, given the good results achieved in recent years both in terms of covering the code that implements a protocol and in terms of finding bugs that can cause security breaches. This paper presents preliminary findings resulting from the investigation of existing fuzzers for the TLS protocol, with the ultimate objective of modifying one of them for testing a new security protocol. It is shown that not all existing fuzzers are functional and that, among those that actually work, the tlsfuzzer deserves attention as the one to be adapted to verify the implementation of the SPDM protocol.